Seismic Performance and Design Method of Novel Resilient Outriggers. Issue 2 (3rd April 2022) - Yang, Qingshun; Fei, Yifan; Tian, Yuan; Lu, Xinzheng
Abstract: A novel seismic resilient outrigger was developed in this study, which is composed of high-strength steel chords with reduced beam sections (RBSs) and buckling restrained braces (BRBs). This energy-dissipating outrigger had a good deformation capacity and stable load-bearing capacity. Its chords remained elastic under the maximum considered earthquakes. Compared with conventional outriggers, it had a better energy dissipation capacity and seismic resilience. Experiments and finite element analyses were used to study the overall seismic performance of the resilient outrigger and deformation performance of the RBSs under the axial-flexural-shear coupling action, and the design method for the RBSs under this axial-flexural-shear coupling action was established. The seismic design method and details of the resilient outrigger are presented.